Initiation and engagement as mechanisms for change caused by collaborative care in opioid and alcohol use disorders. (1st November 2018) - Setodji, Claude M.; Watkins, Katherine E.; Hunter, Sarah B.; McCullough, Colleen; Stein, Bradley D.; Osilla, Karen Chan; Ober, Allison J.
Highlights: Collaborative care interventions increase the likelihood of abstinence in patients. Treatment initiation, not engagement partially medicated the effect on abstinence. This emphasizes the importance of giving feedback to patients about substance-use. Future work should examine patients with alcohol use disorder alone in this context. Abstract: Background: To assess the mechanism by which a collaborative care (CC) intervention improves self-reported abstinence among primary care patients with opioid and alcohol use disorders (OAUD) compared to treatment as usual. Methods: Secondary data analysis of SUMMIT, a randomized controlled trial of CC for OAUD. Participants were 258 patients with OAUD receiving primary care at a multi-site Federally Qualified Health Center. Using a mediation analysis decomposition of a total effect into a mediated and a direct effect, we examined the effect of CC on abstinence at six months, attributable to the HEDIS treatment initiation and engagement measures for the total sample, for individuals with alcohol use disorders alone, and for those with a co-morbid opioid use disorder. Results: Although the CC intervention led to an increase in both initiation and engagement, among the full sample, only initiation mediated the effect of the intervention on abstinence (3.8%, CI=[0.4%, 8.3%]; 32% proportion of the total effect). In subgroup analyses, among individuals with comorbid alcohol and opioid use disorders, almost 100% of the total effect was mediated by engagement, but the effect was not significant. This was not observed among the alcohol use disorder only group. Conclusions: Among primary care patients with OAUDs, treatment initiation partially mediated the effect of CC on abstinence at 6-months. The current study emphasizes the importance of primary care patients returning for a second substance-use related visit after identification. CC may work differently for people with co-morbid opioid use disorders vs. alcohol use disorders alone.